Soft Power Diplomacy Indonesia dalam Membantu Proses Perdamaian Afghanistan di era presiden joko widodo (2017-2020) - Rizqiyani, Fani Azki; Hartati, Anna Yulia (Kajian Hubungan Internasional, 2023)
This thesis aims to find out the reason for the city of Semarang to establish a sister city cooperation with the city of Brisbane. Globalization is the main reason for various countries in the world to cooperate with each other. It aims to meet the needs of each country. Sistercity exists as a tradition and partnership that is able to make interesting literature and understandable conclusions. The sources in this study were the Chief of Staff of the Inter-Agency Cooperation Section of the Semarang City Government and the Staff of the Foreign Cooperation Section of the Semarang City Government. The procedure used in this research is a qualitative approach, where the researcher places more emphasis on analysis as well as a description of the existing state of reality so that the results of this research create a lot of descriptive information in the form of words. the Similarity of Characteristics or Similarities between the two Regions/Cities. The results of the study show why the Semarang City Government establishes this sister city collaboration because of the similarity of characteristics and similarity of interests. In the process of cooperation, the MoU was signed in 1993 but in 2003-2012 it was temporarily suspended. This happened because Indonesia experienced a crisis that year which hampered cooperation between the two countries. However, in 2012 the collaboration was finally re-established which had stopped. Both countries felt the benefits and good impacts of the cooperation.